2019
DOI: 10.1002/jbm.a.36670
|View full text |Cite
|
Sign up to set email alerts
|

Modulating cancer cell mechanics and actin cytoskeleton structure by chemical and mechanical stimulations

Abstract: To date, a myriad of strategies has been suggested for targeting the chemical signaling of cancer cells. Also, biomechanical features are gaining much more attention. These features can be used as biomarkers which influence cancer progression. Current approaches on cancer treatment are mainly focused on changing the biochemical signaling of cancer cells, whereas less attention was devoted to their biomechanical properties. Herein, we propose targeting of cancer cell mechanics through the microenvironmental mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 40 publications
0
20
1
Order By: Relevance
“…A similar work on breast cancer cells using matrices of different rigidity discovered a direct correlation between migration capacity and increase of matrix stiffness (83). Moreover, cells treated with cetuximab, an epidermal growth factor receptor (EGFR) inhibitor, had an increased elastic modulus followed by a decrease in migration ability.…”
Section: Regulation Of Cancer Resistance Through Cellular Stiffnessmentioning
confidence: 94%
See 1 more Smart Citation
“…A similar work on breast cancer cells using matrices of different rigidity discovered a direct correlation between migration capacity and increase of matrix stiffness (83). Moreover, cells treated with cetuximab, an epidermal growth factor receptor (EGFR) inhibitor, had an increased elastic modulus followed by a decrease in migration ability.…”
Section: Regulation Of Cancer Resistance Through Cellular Stiffnessmentioning
confidence: 94%
“…Moreover, cells treated with cetuximab, an epidermal growth factor receptor (EGFR) inhibitor, had an increased elastic modulus followed by a decrease in migration ability. Here, the authors explained that cell mechanics are not only regulated by mechanical cues of the ECM but also by biochemical signals mediated through membrane receptors, such as EGFR (83).…”
Section: Regulation Of Cancer Resistance Through Cellular Stiffnessmentioning
confidence: 99%
“…More recently, hypoxia has been shown to alter cancer cell force generation through RhoA- 1 6 ROCK signaling (7). Other essential factors in the tumor microenvironment such as epidermal growth factors have been shown to modulate cancer cell mechanotype including local cell elasticity, actin cytoskeleton architecture, and cell migration (12). It will be interesting in future work to define the interplay among multiple signals that activate RhoA-ROCK (57) to regulate cancer cell behaviors in the complex tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical cues, such as increased matrix stiffness in tumors, cause cancer cells to increase their stiffness and force production (8)(9)(10). While various soluble and mechanical cues are known to regulate cancer cell mechanotype (11,12), our knowledge of the shared molecular mediators that regulate cellular mechanotype and functional behaviors to drive metastasis is still emerging.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical signals from the surrounding environment play a vital role in regulating tumor cell behavior (Chaudhuri et al, 2018; Emon et al, 2018). Specifically, in vitro studies have shown that tumor cell migration and motility are strongly affected by the substrate mechanics (Azadi, Tafazzoli‐Shadpour, et al, 2019; van Helvert et al, 2018). Significant efforts have been spent on investigating the alteration of tumor cell structural and biological behavior in response to the rigidity of the cellular substrate such as change in cell morphology, adhesion, stiffness, protein expression, migration, and motility (Azadi, Tafazzoli‐Shadpour, et al, 2019; Jiwlawat et al, 2019; Pandamooz et al, 2020; Rice et al, 2017a; Shukla et al, 2016).…”
Section: Introductionmentioning
confidence: 99%